The effect of spirulina (Arthrospira platensis) (Oscillatoriales: Cyanobacteria) on the experimental breeding of Pseudosuccinea columella (Basommatophora: Lymnaeidae) - Prepelitchi, Lucila (2015)
Snails of the family Lymnaeidae, as Pseudosuccinea columella, are the intermediate hosts of Fasciola hepatica, the causative agent of fasciolosis in human and livestock all over the world. A thorough knowledge of snail biology is essential for describing the transmission dynamics and for controlling this disease. Since food quality has had a significant effect on snail growth, fecundity and fertility, in this study we evaluated the use of spirulina (Arthrospira platensis) as a food resource for the artificial breeding of P. columella, an invasive snail and the main intermediate host of F. hepatica in Northeastern Argentina. The main purpose was to measure the effect of spirulina on fitness parameters such as survival rate, growth rate, size at first reproduction, lifetime fecundity and viable offspring. A total of 20 676 newly-laid F2 eggs were used; half of them were fed with lettuce (treatment L) and the other half with lettuce plus spirulina (treatment L+S). In comparison with P. colu- mella snails fed only with lettuce, we found that P. columella fed with lettuce plus spirulina: 1) showed higher survival rates, 2) grew faster and showed higher growth increments, 3) attained sexual maturity earlier in time (L+S:60 days vs. L:120 days) and at a smaller size (L+S:4.8mm vs. L:8.2mm), 4) had a longer reproductive period (L+S:150 days vs. L:90 days), 5) produced a higher number of eggs/snail (L+S:29.6 vs. L:13.3), and 6) showed a higher offspring hatching rate (L+S:70% vs. L:40%). The supplementation of P. columella diet with commercial spirulina enhances it fitness and improved the artificial breeding of this species. Spirulina may have a direct positive effect on P. columella development by consuming it, along with an indirect positive effect by improving the water quality. This rearing technique provided large number of reproducing adults and a continu- ous production of offspring, which are essential for developing future experimental studies in order to improve our knowledge on P. columella biology.